Juvenile delinquency : - McNamara, Robert Hartmann (McGraw-Hill, 2014)
Juvenile Delinquency: Bridging Theory to Practice brings together academic learning and practical exposure to real-life events in a way that empowers students to better understand how what they learn in-class applies to the larger criminal justice picture. Author and professor, Robert McNamara facilitates a learning process that goes beyond memorization to engagement with relevant, practical social applications and analyses. Students’ critical thinking skills are strengthened by studying actual case studies, and applying what they’ve learned to determine the best course of action. Additionally, video assignments that include footage of actual juveniles in detention and practitioners will question preconceptions and myths that students may have. Juvenile Delinquency: Bridging Theory to Practice breaks down the barriers between theory and practice, and allows students to connect with course material in a whole new way.